2012
DOI: 10.4103/0973-6247.98939
|View full text |Cite
|
Sign up to set email alerts
|

Deferral pattern in voluntary blood donors on basis of low hemoglobin and effect of application of digital hemoglobinometer on this pattern

Abstract: Background:One of the responsibilities of blood center is to provide safety to blood donors. It is mandatory to screen a blood donor for hemoglobin (Hb) or hematocrit which should not be less than 12.5 g/dl or 38% Hct. Most commonly applied method for hemoglobin estimation is copper sulphate method, but this method has chances of false acceptance as well as false deferral. In order to avoid this chance of error, digital hemoglobinometer is used. This study was planned to analyze effect of application of digita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…As the copper sulfate density-based hemoglobin screening procedure has been demonstrated to be fraught with low sensitivity in detecting negative iron balance,[ 19 20 ] blood donor recruitment centers should be encouraged to adopt hemoglobin meters for hemoglobin screening during mobile sessions to ensure adequate protection of prospective donors. [ 21 ]…”
Section: Discussionmentioning
confidence: 99%
“…As the copper sulfate density-based hemoglobin screening procedure has been demonstrated to be fraught with low sensitivity in detecting negative iron balance,[ 19 20 ] blood donor recruitment centers should be encouraged to adopt hemoglobin meters for hemoglobin screening during mobile sessions to ensure adequate protection of prospective donors. [ 21 ]…”
Section: Discussionmentioning
confidence: 99%
“…Inaccuracy in capillary haemoglobin could contribute to exacerbate the problem of donor rejection, and we and others have shown that many donors with acceptable haemoglobin concentration are inappropriately deferred under the conditions of routine fingerstick screening . Such imprecision may be related to analytical and non‐analytical factors such as the devices and procedures used for measurements, donor's posture for blood sampling, season of the year and intrinsic donor characteristics , but it can also be due to inherent differences between capillary and venous blood samples .…”
Section: Discussionmentioning
confidence: 99%
“…[ 4 5 6 7 ] Significant focus of WHO, NACO, AABB and Central Drugs Standard Control Organization has been to design and implement a stringent donor selection criteria both to ensure donor's and recipient's safety. Several studies have shown the anemia as the single largest cause of donor deferral with quantum of deferral ranging from 12.4% to 26%[ 8 9 10 11 ] in India. NC associated with Hb estimation might lead to the person who is already anemic to donate blood and in effect increasing the severity of anemia.…”
Section: Discussionmentioning
confidence: 99%